Pengaruh Penambahan Ampas Tebu Terhadap Performa Maggot Black Soldier Fly (Hermetia Illucens) - Siti Hazar; Mufid Dahlan; Wenny Ladhunka Nur Aliyya (Musamus Journal of Livestock Science, 2022)
Maggot black soldier fly (Hermetia illucens) is a black soldier fly larva that is often found in grass and leaves, has a chewy texture, and is able to naturally secrete amylase enzymes. Organic waste from fruit waste and bagasse has the potential to damage the environment but can be used as maggot feed. This study aims to determine the effect of adding bagasse on the performance of the maggot black soldier fly (Hermetia illucens). This research was conducted from April 1, 2022, to April 29, 2022, at UPT Agroscience Technopark, Faculty of Animal Husbandry, Lamongan Islamic University, Jl. Veteran No. 53 A Lamongan, Kab. Lamongan, East Java. The research method used RAL, namely 4 treatments and 3 replications. With the number population, the data taken include population density, weight and maggot length. The results of the study with a population of p1: 276, p2: 234 and p3: 202 tails. It was found that the average maggot population density was 0.005 fish/cm2, the average maggot weight was 35 grams, and the maggot length averaged 21.61 mm.